Prevalence of Cardiovascular Risk Factors in the Population of the Area I in the Municipality of Cienfuegos - Hilda María Delgado Acosta; Karelis Lastre Navarro; María Lina Valdés Gómez; Mikhail Benet Rodríguez; Alain Morejón Giraldoni (Universidad de las Ciencias Médicas de Cienfuegos, 2014)
Background: since the beginning of the epidemiological transition, there was a prevalence of morbidity and mortality from non communicable diseases, mainly cardiovascular disease. Objective: to identify the prevalence of cardiovascular risk factors in the population of the Area I in the municipality of Cienfuegos during 2010-2011. Methods: a descriptive cross-sectional study was conducted to determine the prevalence of cardiovascular risk factors in the population of the Area I in Cienfuegos by means of a complex three-stage equal probability sample of 581 people. The sampling units consisted of districts, areas and sections containing the dwellings where the subjects were chosen. A survey with the following variables was applied: age, sex, marital status, skin color, history of hypertension and diabetes mellitus, smoking, physical activity, food intake (fruits, vegetables and fat), body mass index and waist circumference. Results: 35-44-year age group and female sex predominated, as well as white married individuals. Prevalence of diabetes mellitus and smoking was 6.4% and 28.6%, respectively. Only 26.2% of the respondents were engaged in adequate physical activity. Consumption of fruits was 61.3%. Prevalence of hypertension was 33.8%. Conclusions: The risk factors were more prevalent in females, except for smoking and hypertension; they were more evident with increasing age. Role of hypertension as a tracer condition closely related to cardiovascular risk factors was demonstrated.